Pengaruh Layanan Konseling Kelompok Dengan Teknik Sosiodrama Terhadap Pelaku Bullying Siswa - Nani Barorah Nasution; Sami Sarah Samosir (INDONESIAN COUNSELING AND PSYCHOLOGY, 2021)
This study aims to determine the Effect of Group Counseling Services with Sociodrama Techniques on Bullying Actors for Class VII Students of SMP Negeri 27 Medan T.A 2020/2021. The formulation of the problem in this study is: Is there an Influence of Sociodrama Technique Group Counseling Services on Bullying Actors for Class VII Students of SMP Negeri 27 Medan T.A 2020/2021. The method used in this study is a quantitative method. This type of research is a quasi-experimental with the type of pre-test-post-test one group design. This research was conducted from August to September 2020. The population in this study were all seventh grade students. The sample in this study was class VII-I students who were taken by purposive sampling method consisting of 8 students. The instrument used is a questionnaire to find out the perpetrators of student bullying. The instrument was given before and after the implementation of the sociodrama technique group counseling service. Then the data was analyzed using the Wilcoxon test to see if there was a significant effect of providing sociodrama technique group counseling services on student bullying perpetrators. This can be obtained from the calculation results with the initial test score (pre-test) in the experimental group obtained an average of = 167.5 while the post-test data obtained an average of = 94. This can be obtained from the Wilcoxon test which shows that the level test Wilcoxon obtained Jcount = 75 while Jtable = 4. From the table of critical values . J for the Wilcoxon-signed level test for n = 8, = 0.05 according to the criteria with acceptance and rejection of the hypothesis, the hypothesis is accepted if Jcount> Jtable, namely Jcount>Jtable where 75>4, from this calculation it can be seen the effect of treatment in the experimental group, it means that the influence of sociodrama technique group counseling is more significant (75>4). This means that the hypothesis which reads that there is a significant effect of providing group counseling services with sociodrama techniques on bullies for Class VII students of SMP Negeri 27 Medan for the 2020/2021 academic year can be accepted